Penerapan Metode Simple Additive Weighting (SAW) dan Rank Order Centroid (ROC) dalam Keputusan Pemberian Kredit Sepeda Motor - Dwika Asrani; Rima Tamara Aldisa; Gunawan Siburian; Jannus Manik (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Motorcycle credit is a method of borrowing money from a financial institution, such as a bank or finance company, to buy a motorcycle. Naira Finance, as one of the leading finance companies in Indonesia, provides convenience for customers to own vehicles (both new and used motorcycles) of various brands. The job of a motorcycle loan manager is to decide whether or not to provide motorcycle loans to customers. To reduce the possibility of customer negligence in paying credit bills in the future, it is important to provide credit on time. As a supporting effort, credit managers should use a computer-based application known as a Decision Support System (DSS) to make credit granting decisions more accurate. A computer-based system known as SPK can assist managers in making both structured and unstructured decisions. Researchers try to combine the Rank Order Centroid (ROC) method and the Simple Additive Weighting (SAW) method when deciding to give credit or not to customers. In preference to the SAW method of calculation, it is intended that the weighting results of the ROC method are significant. the results of the decision from the application of the ROC and SAWt methods, there are 5 alternatives that are accepted to receive credit because they are considered feasible and meet the requirements criteria specified as customers who are entitled to receive credit while the other 5 alternatives are rejected so that they are declared unable to receive credit because they do not meet the customer requirements criteria.